Village Mothers, City Daughters : Women and Urbanization in Sarawak - Hew, Cheng Sim (Book collections on Project MUSE., 2007)
Presents a collection of studies on the experiences of women as they encounter the forces of modernization altering the face of contemporary Borneo. Discusses the pressing issue of urbanization and rural-urban migration as experienced by women in Southeast Asia.